Pengaruh Kondisi Sosial Ekonomi, Pendidikan Orang Tua, dan Prestasi Belajar terhadap Motivasi Melanjutkan Pendidikan ke Perguruan Tinggi - Muhammad Rois Al Amin; Masduki Zakaria (Journal of Information Technology and Education (JITED), 2025)
This study aims to analyze (1) the effect of socioeconomic conditions on motivation to continue education to higher education. (2) the influence of parental education on the motivation to continue education to higher education. (3) analyze the effect of learning achievement on motivation to continue education to higher education. This type of research is ex post facto. The population in this study were XII grade students majoring in Computer Network Engineering (TKJ) SMK LPPM RI 2 Kedungreja, totaling 62 students. The sampling technique is total sampling. Instruments are questionnaires and documentation. Data analysis techniques using multiple linear regression analysis. The results of the study (1) There is a positive and significant influence of socioeconomic conditions on motivation to continue education to higher education, p-value <0.05, contribution of 18.21%. (2) There is a positive and significant effect of parents' education on motivation to continue education to higher education, p-value <0.05, contribution of 40.93%. (3) There is a positive and significant effect of learning achievement on motivation to continue education to higher education, p-value <0.05, contribution of 12.26%.